The Effect of Traditionally Combustion Method of Bamboo Leaves Ash in Concrete Mixtures - Suratama, Susana M.; Febriyani, Elisabeth R.; Nday, Albert Aun Umbu (Politeknik Sukabumi, 2023)
Rapid industrialization, households, and commerce emerging waste problems. Not only in urban societies but also in rural communities. The rural communities receive waste from their environmental condition of agro-industrial waste such as bamboo leaves. The leaves are usually dried and burned in open spaces. Former studies concluded that silica content can be found in rice husks, bamboo leaves, sugarcane bagasse, and so on by combustion process. The traditional combustion method is a simple method by which burnt bamboo leaves can produce ash with contains more carbon. This study lifted a way to produce more silica by extracting the ash using citric acid. The citric acid supports quick combustion to reduce inorganic and organic material in bamboo leaves. This process resulted in BLA in white color. The BLA substitute the cement content of concrete with composition of 0%, 7%, 8%, and 9%. The parameter in this study is to measure the density of concrete mixtures by using UPV apparatus and to measure the strength of concrete compressive by using a compression machine. The results concluded that the BLA provides a sufficient density of concrete and The BLA concrete strength has decreased with the added amount of BLA. The strength of BLA has contrasted with other studies that described improving the strength of concrete by BLA substitute from 5% to 30%. Therefore, the combustion process is still necessary to improve by taking more time for extraction and combustion process. Also, controlling slump degradation can affect water/ratio which can also affect the concrete strength.